2005
DOI: 10.1111/j.1751-1097.2005.tb01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Fluorescence Imaging of Photosensitized DNA Denaturation in Cell Nuclei

Abstract: The double‐stranded helical structure of DNA is maintained in part by hydrogen bonds between strands and by stacking interactions between adjacent purine and pyrimidine bases in one strand. The transition (denaturation) from a double‐stranded (ds) to a single‐stranded (ss) form can be induced in isolated DNA or fixed cells by exposure to elevated temperatures, alkali or acids, aprotic or nonpolar solvents or some drugs. We report here that DNA denaturation can occur in situ in cell nuclei as a result of intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Located at 18q21, it has three exons and two open-reading frames (promoters), and is closely related to cell apoptosis (Bernas et al, 2005;Yoshida et al, 2006), as well as closely associated with the mitochondrion (Degli Esposti, 2004;Dias and Bailly, 2005). Immunohistochemical study and observation using confocal microscopes and electronic microscopes have shown that Bcl-2 protein is found in various membranes in the cell, such as the nucleus membrane, membrane of the endoplasmic reticulum, and the mitochondrial membrane, with the largest quantity of it being found on the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Located at 18q21, it has three exons and two open-reading frames (promoters), and is closely related to cell apoptosis (Bernas et al, 2005;Yoshida et al, 2006), as well as closely associated with the mitochondrion (Degli Esposti, 2004;Dias and Bailly, 2005). Immunohistochemical study and observation using confocal microscopes and electronic microscopes have shown that Bcl-2 protein is found in various membranes in the cell, such as the nucleus membrane, membrane of the endoplasmic reticulum, and the mitochondrial membrane, with the largest quantity of it being found on the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred microlitre of PBS was added to the samples, which were placed under the confocal laser scanning microscope so that the morphology of the cells can be observed. Dual-channel activation was used for the measurement, with an excitation wavelength of 488 nm and a radiation wavelength of 500-520 nm for PMT1 (AO) and an excitation wavelength of 543 nm and a radiation wavelength of 600-700 nm (Bernas et al, 2005) for PMT2 (EB). Objective APO CS40×/1.25 oil, zoom > 1, pinhole 1.5 Airy, mode XYZ, format 512 × 512.…”
Section: Staining and Observationmentioning
confidence: 99%
“…AO is a membrane permeant nucleic acid stain that intercalates dsDNA and binds to ssDNA as well as to ssRNA through dye-base stacking to give broad spectrum fluorescence when excited at 476 nm (24). This compound stains all cells in a biofilm, live or dead, and may also bind to nucleic acids that are present in the extracellular matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Then 200µl of PBS is added, and LCSM is used to observe the morphology of the cells. Dual-channel activation is used, with an excitation wavelength of 488nm and a radiation wavelength of 500-520nm for PMT1(AO) and an excitation wavelength of 543nm and a radiation wavelength of 600-700nm for PMT2(AO) [16] . Objective APO CS40 /1.25oil, zoom>1, pinhole 1.5 Airy, mode XYZ, format 512 512 , and after the staining solution is sucked out, rinsed 3 times with RPMI1640, after which 150µL of Fluo-3/AM (Molecular Probes) with a concentration of 4µg/mL is added.…”
Section: B Methodsmentioning
confidence: 99%